The work of Daphne Hampson: The God talk of one feminist theologian - Jacobs, Maretha M. (HTS teologiese studies, 2007)
For almost all of human history both in ancient times and in modern contexts, talk about God has been mainly a male preserve. So closely has male God talk been associated by many with God’s own voice, that it is still not commonly realized and acknowledged. With the rise of feminism, especially during recent decades, it has changed. In this article the work of Daphne Hampson, a British feminist theologian, is considered: Her definition and critique of Christianity, her view of the relation between the present and our Christian past, specifically with regard to God talk, her dealing with prominent aspects of the Christian belief system and her emphasis on taking seriously all available knowledge and our contemporary context in doing theology. In line with some current trends in God talk, such as a movement away from anthropomorphism, and in dialogue with Friedrich Schleiermacher, she formulates what she calls a “future theism”.